Small non‐coding RNA sequencing reveals global dysregulation of piwi‐interacting RNA (piRNA) expression in gonadal malignant germ cell tumours. (26th October 2022) - Laidlaw, Sean; Alonso‐Crisostomo, Luz; Bailey, Shivani; Saini, Harpreet K.; Molnár, Attila; Nicholson, James C.; Enright, Anton J.; Scarpini, Cinzia G.; Rahbari, Raheleh; Coleman, Nicholas; Murray, Matthew J.; ,
Abstract: Background: Analyses of small non‐coding RNA (ncRNA) expression in malignant germ cell tumours (GCTs) have focused on microRNAs (miRNAs). As GCTs all arise from primordial germ cells, and piwi‐interacting RNAs (piRNAs) have important roles in maintaining germline integrity via transposon silencing, we hypothesised that malignant GCTs are characterised by fundamental piRNA dysregulation. Aims: We undertook global small ncRNA sequencing in malignant GCTs, in order to describe small ncRNA expression changes for both miRNAs and piRNAs. Materials and methods: We performed small ncRNA next generation sequencing on a representative panel of 47 samples, comprising malignant GCT ( n = 31) and control ( n = 16) tissues/cell lines. Following quality control and normalisation, filtered count reads were used for differential miRNA and piRNA expression analyses via DESeq2 . Predicted mRNA targets for piRNAs were identified and utilised for pathway enrichment analyses. Results: Overall, miRNAs and piRNAs comprised 21.9% and 43.0% of small ncRNA species, respectively. There were 749 differentially expressed miRNAs in malignant GCTs, of which 536 (72%) were over‐expressed and 213 (28%) under‐expressed. The top‐ranking over‐expressed miRNAs were exclusively from the miR‐371∼373 and miR‐302/367 clusters. The most significantly under‐expressed miRNAs were miR‐100‐5p, miR‐214‐3p, miR‐125b‐5p and let‐7 family members, including miR‐202‐3p. There were 1, 121 differentially expressed piRNAs in malignant GCTs, of which 167 (15%) were over‐expressed and 954 (85%) under‐expressed. Of note, of the top‐20 differentially expressed piRNAs, 16 were over‐expressed, of which piR‐hsa‐2506793 was both top‐ranking and most abundant. Mobile element (ME; i.e., transposon)‐associated piRNAs comprised 166 (15%) of the 1, 121 differentially expressed piRNAs, of which 165 (>99%) were down‐regulated. The remaining 955 (85%) non‐ME‐associated piRNAs may have wider cellular roles. To explore this, predicted mRNA targets of differentially expressed piRNAs identified putative involvement in cancer‐associated pathways. Conclusion: This study confirms previous miRNA observations, giving credence to our novel demonstration of global piRNA dysregulation in gonadal malignant GCTs, through both ME and non‐ME‐associated pathways, which likely contributes to GCT pathogenesis.